Life sciences for the non-scientist - Viqar Zaman (World Scientific, 2005)
As diverse as they are interesting, the issues within the life sciences never fail to impress and stir controversy among the lay public. In a field that too often presents the general reader with challenging and confusing material, this book provides a breath of fresh air: a readable, standalone collection of essays that navigate the complex terrain of cells, cloning, and Mad Cows.